Usefulness of the selected parameters of the Colour Doppler technique in differential diagnosis of breast lesions - Dębniak, Bogusław (Contemporary Oncology/Współczesna Onkologia, 2003)
Angiogenesis is an important factor involved in the development of human malignancies. One of the reasons is that simple diffusion allows for tumor growth up to 2–3 mm in size. The aim of the study was to evaluate the significance of the number of blood vessels in breast lesions and significance of the Vsum value in these vessels in differential diagnosis of benign and malignant breast tumors. Two groups of patients were examined: 75 women with breast cancer and 120 women with benign breast tumors. In the group of breast cancer cases, the absence of blood perfusion was recognized in 4% of patients; while in the second group – in 32.8%. The difference between the mean number of vessels detected in malignant tumors (4) and in benign lesions (1.8) was statistically significant (p<0.0001). The mean Vsum value recorded in malignant tumors was 81.7 cm/s and was over three times higher in comparison to benign lesions (25.35 cm/s). This difference was also statistically significant (p<0.0001). In conclusion, both features (number of blood vessels and the mean value of Vsum) can be applied in the differential diagnosis of malignant and benign breast tumors.